In vitro versus in vivo effects of triptolide: the role of transcriptional inhibition. Issue 2 (March 2005) - McCallum, Christine; Kwon, Suzy; Leavitt, Penny; Shoop, Wesley; Michael, Bruce; Felcetto, Tom; Zaller, Dennis; O'Neill, Edward; Frantz-Wattley, Betsy; Thompson, Chris; Forrest, Gail; Carballo-Jane, Ester; et al.
Background: The mode of action of triptolide, the active ingredient of an anti-inflammatory Chinese herbal remedy, has been investigated in vitro and in vivo . Prior reports suggested that triptolide specifically inhibits the nuclear transcription factor (NF)-κκB. . Methods: In vitro effects of triptoilde on cytokine release and cellular transcription were measured in A549 and THP-1 cells by enzyme-linked immunosorbent assay and incorporation of radiolabeled uridine, respectively. Levels and translocation of the transcription factor NF-kB in vitro were monitored by western blot. Arthritic mice were treated with triptolide, up to 0.5  mg/kg/day for 21 days, and inflammation was evaluated. Taqman analysis was performed on RNA isolated from the arthritic paws to determine relative levels of various cytokines in response to in vivo triptolide treatment. Results: In vitro, triptolide inhibited cellular transcription in A549 and THP-1 cells with IC50 values of 139  nM and 105  nM, respectively, similar to that for inhibition of cytokine release. Nuclear translocation of the transcription factor NF-κκB was not inhibited, and IκκB levels were reduced in response to triptolide exposure. Transcriptional inhibition was not limited to transcripts under the control of NF-κκB, but rather appeared to be a general effect. Triptolide suppressed luciferase expression driven by NF-κκB, AP-1, mouse mammary tumor virus and glucocorticoid response element with various stimuli. Nuclear run-on illustrated that de novo synthesis of RNA was inhibited by 50% in nuclei from cells treated with 50  ng/ml triptolide, while addition of triptolide to isolated nuclei had no effect on transcription. In vivo administration of triptolide reduced mouse plasma tumor necrosis factor-αα levels with long-lasting results. However, monocytes isolated from these triptolide-treated mice showed no impaired RNA synthesis. Efficacious doses of triptolide in a collagen-induced arthritis model in mice reduced the transcript levels of interleukin (IL)-1b, IL-6, p38, and tumor necrosis factor-αα in paws by only 5, 3.5, 1.8 and 1.6-fold, respectively, as determined by Taqman analysis. Mice treated with 0.5  mg/kg/day triptolide for 21 days had arthritis scores lower than those treated with methotrexate. These repeatedly treated mice exhibited no toxicity, and had blood cell counts within normal limits. Conclusion: Thus, despite the transcriptional inhibition in tissue culture, the in vivo mode of action of triptolide cannot be attributed to general inhibition of RNA synthesis, nor strictly to inhibition of NF-κκB signaling, and remains to be elucidated.